2020
DOI: 10.3390/foods10010035
|View full text |Cite
|
Sign up to set email alerts
|

Pomological, Sensorial, Nutritional and Nutraceutical Profile of Seven Cultivars of Cherimoya (Annona cherimola Mill)

Abstract: In this work, the food quality of four international (Campas, Chaffey, Fino de Jete and White) and three local (Daniela, Torre1 and Torre2) cultivars of Cherimoya (Annona cherimola Mill) was investigated. With this aim, pomological traits, sensorial attributes, physiochemical parameters (pH, total soluble content and total acidity), nutritional composition (macro- and micro-nutrients) and nutraceutical values (bioactive compounds, radical scavenging and antioxidant properties) were evaluated. Among the seven o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 79 publications
3
27
0
Order By: Relevance
“…Originally, the assay was studied with the aim to detect and quantify PACs from cranberry samples and correlate their content with potential antimicrobial activity against uropathogenic Escherichia coli [ 83 ]. However, after several experimental studies, the high reproducibility and analytical precision of BL-DMAC was demonstrated, also using different typologies of plant raw materials [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ] and their derived products [ 47 , 64 , 103 , 104 , 105 ]. Since the PAC determination occurs at 640 nm, this assay is less affected by the presence of other phytochemicals, including anthocyanins [ 83 ].…”
Section: Analytical Methods For the Identification And Quantification Of Proanthocyanidinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, the assay was studied with the aim to detect and quantify PACs from cranberry samples and correlate their content with potential antimicrobial activity against uropathogenic Escherichia coli [ 83 ]. However, after several experimental studies, the high reproducibility and analytical precision of BL-DMAC was demonstrated, also using different typologies of plant raw materials [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ] and their derived products [ 47 , 64 , 103 , 104 , 105 ]. Since the PAC determination occurs at 640 nm, this assay is less affected by the presence of other phytochemicals, including anthocyanins [ 83 ].…”
Section: Analytical Methods For the Identification And Quantification Of Proanthocyanidinsmentioning
confidence: 99%
“… Cluster distribution of proanthocyanidins based on the total proanthocyanidin content within plant families and according to previously published data [ 96 , 97 , 99 , 100 , 101 , 102 , 104 , 105 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ]. Euclidean distances were calculated with the average linkage method.…”
Section: Figurementioning
confidence: 99%
“…A. cherimola and A. squamosa fruits are sweeter than A. muricata , A. reticulata, and A. macroprophyllata . They have a low content of lipids and proteins [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Furthermore, the pulp exhibits a good quantity of dietary fiber, although A. muricata and A. cherimola fruits are more fibrous.…”
Section: Agronomic Knowledgementioning
confidence: 99%
“…On the other hand, the nephrotoxicity, carcinogenicity, cytotoxicity, and teratogenicity of citrinin are well known even at a very low dosage [20]. For these reasons, in the last few decades, the research of new medicinal plants as an alternative approach for the treatment of hypercholesterolemia is on-going [21][22][23]. In particular, attention is focused on the identification of new phytochemicals that may exert an antihypercholesterolemic action through a different mechanism of action from what has been reported for statins [24].…”
Section: Introductionmentioning
confidence: 99%